2010
DOI: 10.1002/lary.20873
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the evidence for the etiology of adult sudden sensorineural hearing loss

Abstract: The suspected etiologies for patients suffering sudden sensorineural hearing loss included idiopathic (71.0%), infectious disease (12.8%), otologic disease (4.7%), trauma (4.2%), vascular or hematologic (2.8%), neoplastic (2.3%), and other causes (2.2%). Establishment of a direct causal link between SSNHL and these etiologies remains elusive. Diagnostic imaging is a useful method for identification of temporal bone or intracranial pathology that can present with SSNHL as a primary symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
378
1
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(399 citation statements)
references
References 33 publications
2
378
1
18
Order By: Relevance
“…It is possible to recognise a specific aetiology only in about 10% of cases (Nosrati-Zarenoe et al, 2007;Chau et al, 2010); however, to explain the inner ear damage, several pathogenetic mechanisms were proposed such as vascular, viral, autoimmune, traumatic and metabolic. Impaired cochlear perfusion remains the most supported hypothesis due to the characteristics of inner ear circulation, constituted by a terminal capillary bed without collateral blood supply; vasospasm, thrombosis or vascular haemorrhage may be responsible of a reduced cochlear blood flow with consequent hypoxia, decrease of metabolic activity and damage of cochlear hair cells (Mosnier et al, 2010;Martines et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to recognise a specific aetiology only in about 10% of cases (Nosrati-Zarenoe et al, 2007;Chau et al, 2010); however, to explain the inner ear damage, several pathogenetic mechanisms were proposed such as vascular, viral, autoimmune, traumatic and metabolic. Impaired cochlear perfusion remains the most supported hypothesis due to the characteristics of inner ear circulation, constituted by a terminal capillary bed without collateral blood supply; vasospasm, thrombosis or vascular haemorrhage may be responsible of a reduced cochlear blood flow with consequent hypoxia, decrease of metabolic activity and damage of cochlear hair cells (Mosnier et al, 2010;Martines et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] However, the exact incidence of SSHL is higher because a large portion of patients heal spontaneously without medical and surgical treatment [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Different theories have been proposed to explain the etiology. These include, for example, bacterial, viral, and protozoan infections, vascular occlusion, mechanisms associated with the immune system, ototoxicity drugs (salicylates, aminoglycosides) and traumatic, vascular, neoplastic, and metabolic conditions [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A higher blood viscosity may determine damage in ear microcirculation that can produce hearing loss [16,17]. Ciccone et al showed that ISSHL seemed to be associated with vascular endothelial dysfunction and preclinical atherosclerosis by calculating the carotid intima-media thickness [18].…”
Section: Discussionmentioning
confidence: 99%